SAT0001 Multicentric Study of Cognitive Impairment in Sle: the Ecles Study. (10th June 2014) - D'Amico, A.; Galván, L.S.; Romero, J.; Arturi, V.; Collado, M.V.; Gόmez, G.; Spindler, A.; Rojas, G.; Fillippin, F.; Vita, L.; Cόrdova, R.; Panόpulos, A.; et al.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) have an increased risk of cognitive impairment (CI) of 39-46% compared to healthy individuals and it may be due to the disease, its complications, its therapy or associated comorbidities. Objectives: To determine the frequency and characteristics of CI in lupus patients without known previous NP events. Methods: Patients aged 16-51 fulfilling 1997 criteria for SLE enrolled from 06/2012 to 07/2013 were included. The ACR battery was used to determine CI, the Cognitive Symptoms Inventory (CSI) and Beck depression were also assessed. CI was defined as ≤2 standard deviations compared to the general population in at least one test. It was considered a focal (CIf) involvement if it affected one or more measures of a single domain and multifocal (CIm) if 2 or more domains were affected. To compare proportions, Fisher's exact test was used and to compare numerical variables, Kruskal-Wallis. A value of p<0, 05 was considered significant. Results: Eighty-six patients were evaluated, 94% were female, median age 36 years (16-51), 90% were Caucasian, 8% mestizos and 1% Amerindian. Eighty % had high school. Median SLEDAI was 2.5% (0-24) and median SLICC 0 (0-8).CI was found in 65% of patients (56/86), focal (CIf) 32.5% (28/56) and multifocal (CIm) in the same rate. The affected domains were: memory 45%, executive functions 30%, attention 29% and language 4.6%.Depression was detected in 48% of patients. Risk factors were analyzed for the different groups: without CI (n=30), CIf (n=28) and CIm (n=28) although we found no statistically significant difference except for ethnicity (table 1). Non-Caucasian patients had a higher median SLEDAI of 8 (2-24), median duration of disease 10 (1-31), although CI was not associated with the number of years of education. Conclusions: A high frequency of CI was found in patients with SLE, non-Caucasian had higher CI with significant differences. Patients with CI had a longer history of the disease without reaching statistical significance, and it was not related to the number of years of education or with rates of depression. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2616